Evaluation of the enzyme inhibitory and antioxidant activities of Entada spiralis stem bark and isolation of the active constituents - Opeyemi Roheem, Fatimah; Mat So'ad, Siti Zaiton; Ahmed, Qamar Uddin; Ali Shah, Syed Adnan; Latip, Jalifah; Zakaria, Zainul Amiruddin (Molecular Diversity Preservation International (MDPI), 2019)
Digestive enzymes and free radical inhibitors are used to prevent complications resulting from diabetes. Entada spiralis (family Leguminosae), which is a well-known medicinal plant in herbal medicine due to its various traditional and medicinal applications, was studied. Crude extracts were successively obtained from the stem bark using petroleum ether, chloroform and methanol as extracting solvents. The antioxidant activity of all the extracts, fractions and isolated compounds were estimated using 2,2-diphenyl-1-picrylhydrazyl (DPPH), β-carotene and 2,2′-azinobis(-3-ethylbenzothiazine-6-sulfonic acid) (ABTS) assays, while digestive enzymes inhibitory activity was assessed using α-amylase and α-glucosidase inhibitory methods. Structure elucidation of pure compounds was achieved through different spectroscopic analysis methods. Fractionation and purification of the most active methanol extract resulted in the isolation of a ferulic ester namely; (E)-hexyl 3-(4-hydroxy-3-methoxyphenyl) acrylate (FEQ-2) together with five known phenolic constituents, identified as kaempferol (FEQ-3), 5,4′-dihydroxy-3,7,3′-trimethoxyflavone (FEQ-2), gallic acid (FEQ-5), (+)-catechin (FEQ-7) and (−)-epicatechin (FEQ-8). FEQ-5 exhibited the strongest antioxidant and enzyme inhibitory activities followed by FEQ-3 and FEQ-4. FEQ-2 also displayed potent free radical scavenging activity with IC50 values of 13.79 ± 2.13 (DPPH) and 4.69 ± 1.25 (ABTS) µg/mL, respectively. All other compounds were found active either against free radicals or digestive enzymes.